2009
DOI: 10.1002/pon.1653
|View full text |Cite
|
Sign up to set email alerts
|

Can telephone counseling post‐treatment improve psychosocial outcomes among early stage breast cancer survivors?

Abstract: Objective-To determine whether a telephone counseling program can improve psychosocial outcomes among breast cancer patients post-treatment.Methods-A randomized trial was conducted involving 21 hospitals and medical centers, with assessments (self-administered questionnaires) at baseline, 12 and 18 months post-enrollment. Eligibility criteria included early stage diagnosis, enrollment during last treatment visit, and the ability to receive the intervention in English. Endpoints included distress (Impact of Eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
114
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(117 citation statements)
references
References 65 publications
2
114
0
1
Order By: Relevance
“…Progressive muscle relaxation (P.M.R) being one of the non invasive techniques, can be of great help. P.M.R, is one of the cognitive behavioral coping strategies which have been found beneficial in cancer patients also [11,12]. Relaxation is a state of freedom from anxiety and skeleton muscle tension.…”
Section: Introductionmentioning
confidence: 99%
“…Progressive muscle relaxation (P.M.R) being one of the non invasive techniques, can be of great help. P.M.R, is one of the cognitive behavioral coping strategies which have been found beneficial in cancer patients also [11,12]. Relaxation is a state of freedom from anxiety and skeleton muscle tension.…”
Section: Introductionmentioning
confidence: 99%
“…Only one of these studies (46) found significant effects on anxiety, depression, and anger. The other study (47) found no treatment effect on psychological distress, but a significant effect on sexual function and personal growth. The study of Meneses (48) (n: 53) that examined the effects of intervention on quality of life found significant effects on the overall quality of life.…”
Section: • Description Of Included and Excluded Studiesmentioning
confidence: 79%
“…Other approaches have included: self-guided workbooks (Beatty, Oxlad, Koczwara, & Wade, 2010), small group psycho-educational groups (Dolbeault et al, 2009) and telephone counselling (Marcus et al, 2010). None, to our knowledge, have focussed on cancer survivors with moderate depression symptoms.…”
Section: Discussionmentioning
confidence: 99%